Doris Lessing’s Fiction: Literature as Commitment (Altre Modernità, 2014)
-Abstract in lingua inglese: The publication of The Grass Is Singing in 1950 inaugurated the beginning of the long and distinguished literary career of Doris Lessing (1919-2013), the 2007 Nobel laureate for literature. The novel proves to be highly anticipatory in many respects. Firstly, the “eclectic realism” characterizing its formal aspect paves the way to Lessing’s future aesthetic experimentalism and stylistic innovations.Moreover, it also displays several interconnected thematic correspondences with the main motifs informing its author’s entire production and testifies to the oppositional, if not subversive, nature of her works with respect to the normative symbolic foundations of society buttressed within official discourse in England and its colonies from the 1950s onward. Indeed, in giving a voice to those who would tend to be silenced, Lessing turned writing into a privileged site of corrosive social criticism in which she stigmatised numerous forms of oppression, including those that the establishment obscures or secretly condones.Endowed with an “extraordinary barometric sensitivity to the social cli mate”, which allowed her to register minutely – if not foresee – social change, Lessing made her literary intervention the political vehicle for a re-modelling and a re-definition of national (as well as Western) identity paradigms.